2018
DOI: 10.1016/j.jclepro.2017.10.086
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the impacts of urban heat islands. A literature based study on understanding urban heat vulnerability and the need for resilience in cities in a global climate change context

Abstract: The urban heat island (UHI) is a phenomenon whereby temperature levels in urban areas are higher than in surrounding rural settings. Urban heat islands are a matter of increasing concern, since they can affect communities by exacerbating air pollution and greenhouse gas emissions (due to the greater use of air conditioning) and the occurrence of heat-related illness, and may lead to higher levels of mortality. This paper provides a description of the phenomena of (UHI) and an analysis of how cities are vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(79 citation statements)
references
References 61 publications
1
56
0
1
Order By: Relevance
“…Exposure describes to what extent humans, natural assets, or material goods are located in places endangered by climatic changes and their consequences [41]. Some approaches use the exposed population or area as a variable for the risk analysis [42][43][44].…”
Section: Variables For Extreme Heat Exposurementioning
confidence: 99%
“…Exposure describes to what extent humans, natural assets, or material goods are located in places endangered by climatic changes and their consequences [41]. Some approaches use the exposed population or area as a variable for the risk analysis [42][43][44].…”
Section: Variables For Extreme Heat Exposurementioning
confidence: 99%
“…CiteSpace was used to analyze 900 retrieved papers in the "web of science" from 2008 to 2018. We found that only a few research papers adopted methods and processes with control over the sample size, conceptual model, operation mechanism, synchronicity, spatial typicality, weather situation, surface features, and equipment parameters [12,13]. The research content concentrated on the phenomena of UHI (UHI intensity, surface temperature, and atmospheric temperature), their causes (urbanization, land use, and greenbelt), and their influence on the climatic environment.…”
Section: State Of the Artmentioning
confidence: 99%
“…The increase in temperature has enormous negative consequences for the urban population and lowers their quality of life as air and water quality decrease, as well as the thermal comfort. A particular risk comes from the increasing and prolonged heatwaves that lead to a higher number of fatalities [2]. The projected increase in the average annual temperatures suggests an intensification in the UHI effect [3].…”
Section: Introductionmentioning
confidence: 99%